“Evaluación de dos diluyentes comerciales botucrio® e inra96 mediante el proceso de crio preservación de celulas espermaticas en caballos arabe y criollo de 4 a 5 años – en la provincia de Cotopaxi cantón Latacunga” - Garzón Zambonino, Sixto Gabriel (2023)
The research was carried out to evaluate the cryopreservation of equine semen in the province of Cotopaxi, Latacunga Canton, Salache Bajo sector, in the facilities of the Technical University of Cotopaxi, Faculty of Agricultural Sciences and Natural Resources, with the objective of evaluating the sperm characteristics after thawing with the use of two diluents Botucrio® and INRA96 for the conservation and preservation of equine semen from 4 donors among these of Creole and Arabian breeds, a seminal dilution of 1 ml in 1 ml with diluent (Botucrio®) and (INRA 96) as cry preservative was performed, with an initial evaluation of color, odor, pH, aspect, mass motility, individual motility, morphology, sperm concentration, live and dead spermatozoa, using as a basis the packing technique with equine straws, with the adaptation of the straws to temperature gradients until reaching -196°C, the same that corresponds to the preservation medium, sperm values after thawing, its variables in relation to the initial sample. Obtaining a favorable level of integrity pre and post freezing without structural deformation of the semen characteristics. Obtaining an average sperm viability of 80% in the Arabian horse with a better evaluation of semen structure within the post-thawing parameters evaluated by the researcher and his team.